2023
DOI: 10.1101/2023.07.07.23292152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceived and Enacted HIV-Related Stigma in Eastern and Southern Sierra Leone: A Psychometric Study of an HIV Stigma Scale

Abstract: Background: HIV stigma continues to hinder the care of people with HIV (PWH), especially in low-resource settings. We aimed to adapt and validate a concise HIV stigma scale for perceived HIV stigma in Sierra Leone. Methods: We enrolled participants in two HIV clinics in Eastern and Southern Sierra Leone in 2022. We assessed perceived stigma using a 12-item adaptation of Berger's HIV Stigma Scale and enacted stigma using select USAID indicators. We used ordinal logistic regression to identify predictors of perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…6 Regarding the initial version of the instrument, difficulties have been observed in its application due to its large number of items, which can generate fatigue in the participants and difficulties in its use in environments with a large number of patients. 23 In previous research, adequate psychometric properties have been found in more concise versions of the instrument, as reported by Mlouki et al, 24 who identified a 12-item model with 3 dimensions in patients from Tunisia, Africa. Similarly, De los Santos 25 examined the 2-factor structure using 11 items in a US population living with HIV.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…6 Regarding the initial version of the instrument, difficulties have been observed in its application due to its large number of items, which can generate fatigue in the participants and difficulties in its use in environments with a large number of patients. 23 In previous research, adequate psychometric properties have been found in more concise versions of the instrument, as reported by Mlouki et al, 24 who identified a 12-item model with 3 dimensions in patients from Tunisia, Africa. Similarly, De los Santos 25 examined the 2-factor structure using 11 items in a US population living with HIV.…”
Section: Introductionmentioning
confidence: 81%
“…13 On the other hand, although the HIV Stigma Scale has been adapted and translated into different languages such as Spanish, 14 Portuguese, 15,16 Swedish, 17 Urdu, 18 Xhosa, 19 Tamil, 20 Japanese, 21 or Thai. 22 In a meta-analytical study, it is recognized that this instrument exists in multiple versions that vary in the number of items, including 7,8,10,12,13,13,17,18,21,23,25,32, and 39 items, and its internal structure differs even among models with the same number of items, as between 2 and 5 dimensions and various internal structures have been identified. 6 Regarding the initial version of the instrument, difficulties have been observed in its application due to its large number of items, which can generate fatigue in the participants and difficulties in its use in environments with a large number of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation